First record of the opiine genus, Carinopius Tan & van Achterberg, 2016 (Hymenoptera: Braconidae) from India and Thailand with the description of a new species - Ranjith, A.p. (Zootaxa, 2025)
The opiine genus, Carinopius is newly recorded from India and Thailand with the description of a new species, C. dhithyae Ranjith. The genus is previously reported from China and Vietnam. The new species is illustrated along with a revised generic diagnosis and taxonomic key to the extant species.